1998
DOI: 10.1016/s0092-8674(00)81789-4
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the DNA Repair and Replication Endonuclease and Exonuclease FEN-1

Abstract: Flap endonuclease (FEN-1) removes 5' overhanging flaps in DNA repair and processes the 5' ends of Okazaki fragments in lagging strand DNA synthesis. The crystal structure of Pyrococcus furiosus FEN-1, active-site metal ions, and mutational information indicate interactions for the single- and double-stranded portions of the flap DNA substrate and identify an unusual DNA-binding motif. The enzyme's active-site structure suggests that DNA binding induces FEN-1 to clamp onto the cleavage junction to form the prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
269
1
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 251 publications
(276 citation statements)
references
References 57 publications
5
269
1
1
Order By: Relevance
“…As the role of Fen1 in DNA replication and repair is becoming more clear, several groups are interested to structurally characterize this enzyme, and the crystal structures of two archaeal orthologous Fen1 have so far been solved (Hosfield et al, 1998;Hwang et al, 1998). For DNA repair and replication, Fen1's structural recognition of the 5 0 flap is essential.…”
Section: Introductionmentioning
confidence: 99%
“…As the role of Fen1 in DNA replication and repair is becoming more clear, several groups are interested to structurally characterize this enzyme, and the crystal structures of two archaeal orthologous Fen1 have so far been solved (Hosfield et al, 1998;Hwang et al, 1998). For DNA repair and replication, Fen1's structural recognition of the 5 0 flap is essential.…”
Section: Introductionmentioning
confidence: 99%
“…Although a similar hole is present in the Methanococcus jannaschii homologue (9), this region often appears disordered (6, 7) or as a folded loop in the structure of the Pyrococcus furiosus homologue (10). The conceptual model for flap endonuclease-DNA binding has been widely accepted (1,7,9,10,15,16). Nevertheless, this model suffers from uncertainty with regard to the orientation of the flap substrate duplex because of a lack of experimental data identifying key protein-DNA interactions.…”
mentioning
confidence: 99%
“…It has been suggested that the single-stranded 5Ј tail of such substrates threads through the 5Ј nuclease (4). Several prokaryotic and archaeal flap endonuclease structures have been solved (6)(7)(8)(9)(10). Because none of the reported structures contained bound DNA substrates, the precise mode of nucleic acid binding is unclear.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…While WRN helicase activity is regulated by Cterminal interactions that include TRF2 (Opresko et al, 2002), Rad52 (Baynton et al, 2003) and PARP-1 (von ). An example of WRN stimulation of partner proteins includes the FEN-1 partner protein, whose structures with DNA and PCNA have been defined (Hosfield et al, 1998,Chapados et al, 2004. WRN interaction that was mapped to the winged helix domain stimulates FEN-1 nucleolytic activity, by more than 80-fold (Brosh et al, 2001b).…”
Section: Double-strand Breaks Base Excision Repair and Wrnmentioning
confidence: 99%